Kewenangan Notaris dalam Membuat Keterangan Waris yang Berkaitan dengan Aset Digital menurut Hukum Waris di Indonesia - Novya Agitha; Yulia Qamariyanti (Lembaga Yasin AlSys, 2026)
Although the legal status of digital assets has received attention in various previous studies, research that specifically discusses the authority and responsibility of notaries in preparing inheritance certificates related to digital assets within the framework of Western inheritance law in Indonesia remains limited. This study aims to analyze the legal position of digital assets, particularly cryptocurrency and Non-Fungible Tokens (NFTs), as objects of inheritance under inheritance law in Indonesia, and to examine the authority and limits of notarial responsibility in preparing inheritance certificates related to digital assets. This study used a normative legal research method with statutory, conceptual, and analytical approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively, supported by interviews with notarial practitioners. The results show that digital assets with economic value can be classified as intangible movable objects based on Articles 499, 503, and 504 of the Indonesian Civil Code, and therefore may form part of an estate. However, notarial authority is limited to formal aspects, namely the verification of identity, documents, and statements of the appearers, and does not include guaranteeing access to or the transfer of digital assets, which depend on private keys and digital platform policies. Notarial responsibility is limited to formal truth, not material truth regarding the existence, ownership, or accessibility of digital assets. The conclusion of this study emphasizes the importance of comprehensive regulations and standard operating procedures for notaries in handling the inheritance of digital assets. These findings contribute to the development of notarial law in addressing technological challenges and broaden the understanding of the adaptation of inheritance law to digital assets. The implications of this study include theoretical contributions to the literature on notarial law and inheritance law, as well as practical recommendations for the Indonesian Notary Association and policymakers to formulate clear guidelines on the inheritance of digital assets.